Survival in Young-Onset Metastatic Colorectal Cancer: Findings From Cancer and Leukemia Group B (Alliance)/SWOG 80405. (12th October 2021) - Lipsyc-Sharf, Marla; Zhang, Sui; Ou, Fang-Shu; Ma, Chao; McCleary, Nadine Jackson; Niedzwiecki, Donna; Chang, I-Wen; Lenz, Heinz-Josef; Blanke, Charles D; Piawah, Sorbarikor; Van Loon, Katherine; Bainter, Tiffany M; et al.
Abstract: Background: The incidence of young-onset colorectal cancer (yoCRC) is increasing. It is unknown if there are survival differences between young and older patients with metastatic colorectal cancer (mCRC). Methods: We studied the association of age with survival in 2326 mCRC patients enrolled in the Cancer and Leukemia Group B and SWOG 80405 trial, a multicenter, randomized trial of first-line chemotherapy plus biologics. The primary and secondary outcomes of this study were overall survival (OS) and progression-free survival (PFS), respectively, which were assessed by Kaplan-Meier method and compared among younger vs older patients with the log-rank test. Hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated based on Cox proportional hazards modeling, adjusting for known prognostic variables. All statistical tests were 2-sided. Results: Of 2326 eligible subjects, 514 (22.1%) were younger than age 50 years at study entry (yoCRC cohort). The median age of yoCRC patients was 44.3 vs 62.5 years in patients aged 50 years and older. There was no statistically significant difference in OS between yoCRC vs older-onset patients (median = 27.07 vs 26.12 months; adjusted HR = 0.98, 95% CI = 0.88 to 1.10; P = .78). The median PFS was also similar in yoCRC vs older patients (10.87 vs 10.55 months) with an adjusted hazard ratio of 1.02 (95% CI = 0.92 to 1.13; P = .67). Patients younger than age 35 years had the shortest OS with median OS of 21.95 vs 26.12 months in older-onset patients with an adjusted hazard ratio of 1.08 (95% CI = 0.81 to 1.44; P trend = .93). Conclusion: In this large study of mCRC patients, there were no statistically significant differences in survival between patients with yoCRC and CRC patients aged 50 years and older.